A Philosophical Perspective on the Relation between Cortical Midline Structures and the Self - Musholt, Kristina (Frontiers in Human Neuroscience, 2013)
In recent years there has been increasing evidence that an area in the brain called the cortical midline structures (CMS) is implicated in what has been termed self-related processing. This article will discuss recent evidence for the relation between CMS and self-consciousness in light of several important philosophical distinctions. First, we should distinguish between being a self (i.e., being a subject of conscious experience) and being aware of being a self (i.e., being able to think about oneself as such). While the former consists in having a first-person perspective on the world, the latter requires the ability to explicitly represent one’s own perspective as such. Further, we should distinguish between being aware of oneself 'as subject' and being aware of oneself 'as object'. The focus of existing studies investigating the relation between CMS and self has been predominantly on the ability to think about oneself (and in particular thinking of oneself 'as object'), while the more basic aspects involved in being a self have been neglected. However, it is important to widen the scope of the cognitive neuroscience to include the latter, not least because this might have important implications for a better understanding of disorders of the self, such as those involved in schizophrenia. In order to do so, cognitive neuroscience should work together with philosophy, including phenomenology. Second, we need to distinguish between personal and subpersonal level explanations. It will be argued that although it is important to respect this distinction, in principle, some subpersonal facts can enter into constitutive conditions of personal level phenomena. However, in order for this to be possible, one needs both careful conceptual analysis and knowledge about relevant cognitive mechanisms.